Akibat hukum Endorsement Berbasis Instagram terhadap Konsumen : Prespektif Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia - Pratami, Rosa Eza; Bisyri, Mohammad Hasan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Endorsement is a form of cooperation to promote a product, so that sales increase. However, in practice, endorsers only give expressions of praise for the product without a detailed description. This poses a risk to consumers because there is no transparency about product information. The purpose of this study is to explain the legal consequences of endorsements carried out by celebrity endorsers that are detrimental to consumers because they are not transparent in describing the product. The research findings were analyzed with the Fatwa of the National Sharia Council of the Indonesian Ulema Council Number 24 of 2017 concerning the Law of Transactions on Social Media. This empirical legal research uses a qualitative approach. The primary data source was obtained from interviews with celebrity grams @viraveyy, @wmlstr, and @itatahtita. Secondary data sources were obtained from various legal materials and related literature. The results of the study indicate that the implementation of endorsements as a whole is not governed by the provisions of Islamic law because there are still celebrities who are dishonest in promoting products sold on social media, and also several pillars and conditions of the ijarah contract are not perfectly fulfilled. This research is a reference for policymakers related to the issue of Sharia economic law in the contemporary era